The Interaction between Decision and Control Problems and the Value of Information - Arya, Anil; Glover, Jonathan C.; Sivaramakrishnan, K. (The Accounting Review, 1997)
[This paper studies information system design in a model of double moral hazard in which there is both a decision problem and a control problem. If either problem is considered in isolation, an information system that provides more public information is preferred. However, an information system that provides less public information can, in fact, be desirable because of an interaction between the two problems. The benefit of choosing an information system that provides less information is that it serves as a substitute for commitment for the principal. The cost is that neither the principal's decision (act) nor the agent's payments can be conditioned on the information. We provide sufficient conditions under which less information and more information are each optimal.]